The Study Results of Perception and Satisfaction of Elementary School Students with 2D Animation Cartoon: Primal Hunter - Thaluang, Chalantorn; Rungsoongnern, Punyarat (Journal of Applied Informatics and Technology, 2024)
The purposes of this research were to 1) develop the 2D animation cartoon: Primal Hunter, 2) study the perception of the sample group after watching the 2D animation cartoon: Primal Hunter, and 3) study the satisfaction of the sample group after watching 2D animation cartoon: Primal Hunter. The sample group consisted of 56 elementary school students from Ban Nong Buakham School, Nakhon Ratchasima province, selected using a group sampling method. The tools used to collect data were 1) 2D animation cartoon: Primal Hunter, 2) Quality assessment questionnaire for 2D animation cartoon: Primal Hunter, 3) Perception assessment questionnaire for the sample group after watching 2D animation cartoon: Primal Hunter, and 4) Satisfaction measurement questionnaire for the sample group after watching the 2D animation cartoon: Primal Hunter. The statistics used in the data analysis were: percentages, mean, and standard deviations. The study's findings revealed that 1) 2D animation cartoon: Primal Hunter had a very good overall quality, with an average rating of 4.69. 2) The perception level of the sample group after watching the 2D animation cartoon: Pyramol Hunter was found to be 85.36%, indicating a very high level of perception. 3) The satisfaction survey results of the sample group after watching the 2D animation cartoon: Pyramol Hunter showed that the sample group had the highest level of satisfaction, with an average rating of 4.68.